2011
DOI: 10.1371/journal.pone.0023183
|View full text |Cite
|
Sign up to set email alerts
|

Elevated Non-Esterified Fatty Acid Concentrations during Bovine Oocyte Maturation Compromise Early Embryo Physiology

Abstract: Elevated concentrations of serum non-esterified fatty acids (NEFA), associated with maternal disorders such as obesity and type II diabetes, alter the ovarian follicular micro-environment and have been associated with subfertility arising from reduced oocyte developmental competence. We have asked whether elevated NEFA concentrations during oocyte maturation affect the development and physiology of zygotes formed from such oocytes, using the cow as a model. The zygotes were grown to blastocysts, which were eva… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
174
3
2

Year Published

2013
2013
2021
2021

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 240 publications
(190 citation statements)
references
References 63 publications
11
174
3
2
Order By: Relevance
“…Perhaps the best-studied example of a metabolic imprint is for postpartum NEFA and its effect on composition of the oocyte and function of follicular cells Van Hoeck et al, 2011;Wathes, 2012). The possibility that there are permanent epigenetic modifications to the genome during the early postpartum period that affect long-term developmental competence of follicular cells has not been demonstrated at this time.…”
Section: Lucy Butler and Garverickmentioning
confidence: 99%
“…Perhaps the best-studied example of a metabolic imprint is for postpartum NEFA and its effect on composition of the oocyte and function of follicular cells Van Hoeck et al, 2011;Wathes, 2012). The possibility that there are permanent epigenetic modifications to the genome during the early postpartum period that affect long-term developmental competence of follicular cells has not been demonstrated at this time.…”
Section: Lucy Butler and Garverickmentioning
confidence: 99%
“…The marked differences between cows and heifers justify further comparison of their calves. Previous work has demonstrated that the factor 'lactation' alters embryo quality compared with non-lactating cows (Leroy et al, 2005), and that exposure of bovine oocytes to NEB conditions in vitro affects glucose homeostasis in early embryonic stages (Van Hoeck et al, 2011 and. The difference in IGF-I corresponds to other reports (Taylor et al, 2004) and is of particular interest, since IGF-I has been proposed as a mediator between maternal energy balance and foetal development (Wathes et al, 1998;Lucy, 2008;Micke et al, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…A recent study has shown that exposure of the maturing oocytes to elevated concentrations of NEFAs has a negative impact on fertility not only through a reduction in the developmental capacity of the oocyte but also through compromised quality, viability and metabolic capacity of the early embryos (Van Hoeck et al, 2011). The same laboratory suggests that these negative effects of NEFAs on the embryo could be a consequence of modified energy metabolism and particularly, mitochondrial β-oxidation of fatty acids in the oocyte (Van Hoeck et al, 2013). A recent study has shown that bovine cumulus cells are able to protect maturing oocytes from potential harmful effects of increased local concentrations of fatty acids by intracellular storage of lipids (Aardema et al, 2013).…”
Section: Nefasmentioning
confidence: 99%